HUBUNGAN STATUS GIZI DAN STATUS IMUNISASI DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI WILAYAH KERJA PUSKESMAS SOPOSURUNG KECAMATAN BALIGE KABUPATEN TOBA SAMOSIR TAHUN 2014 - Purnama Sinaga; Zulhaida Lubis; Muhammad Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Children are the most vulnerable groups affected by ARI. And in Soposurung the number of children are affected by ARI is increase every year.The aim of this study was to investigate the relationship between nutritional status and immunization status with acute incidence of respiratory infection in infants, to analyze the relationship between exclusive breastfeeding, vitamin A with ARI in infants in Soposurung Public Health 2014.   This type of research is an observational cross-sectional approach. The sample in this study was a toddler as many as 61 people (15 children is ARI and 46 children are not ARI) are taken by using ProbabilitySampling types Alocated Proportional Sampling.   The data were analyzed using Chi-Square statistical test with CI = 95% (α = 0.05), which indicates that there is no significant relationship between nutritional status (W/ A, H/ A and W / H) with ARI in infants (ρ = 0.642; ρ = 0.177 and ρ = 0.377). There is also no significant relationship between exclusive breastfeeding and nutritional status (W / A) ρ = 0.641; nutritional status (H/ A) ρ = 0.693 and for the nutritional status (W/ H) ρ = 0.192. There is a significant association between vitamin A nutritional status (H/ A) ρ = 0.044 and nutritional status (W/ H) ρ = 0.037. However, there is no significant relationship between immunization status with ARI in infants ρ = 0.404.   From this study suggested improving the nutritional status can be improved further, socialization importance of exclusive breastfeeding in infants and setting a good diet early in toddlers.   Keywords: Nutritional status, immunization status, exclusive breastfeeding, vitamine A, Acute Respiratory Infections (ARI)